Quality of life of German senior citizens - Molesztak, Aldona; Błachnio, Aleksandra (Journal of Education, Health and Sport, 2017)
Introduction. As the growing group of 60+ citizens offers more opportunities for research. Researchers have focused on specifying conditions for high quality of life. The following conclusions are can be used for the benefit of individual elderly people as well as the society as a whole. Aim of the study. The conducted research aimed at examining the quality of life of people at the age of 60 and over living in Germany, and specifically at the question about the influence of the elderly people’s opinion about life on their life satisfaction. Resources and methods. The study was conducted in 2012 on the population of 35 senior citizens (20 women and 15 men) who filled in the survey questionnaire, Cantril’s (1965) and Campbell’s Ladder (1976). Every participant filled in the form individually, and the thus collected data were analysed using Statistica 12.5 software. Results. Individuals who found their life satisfying displayed higher scores with respect to future plans, happiness level and appetite for life that people perceiving their life as boring. Analyses of life assessment against the time line have proved significant only in relation to the present and the future. Conclusions. Researchers have pointed out that only 20% of the population automatically and effortlessly reaches the high level gerotranscendence. It has been observed that for the majority of people the process is slowed down or even blocked for various reasons which include expectations towards the old age as a continuation of former existence, isolation, decreasing social network, or disability (Tornstam, 2011).